Prevalence of functional disability in the elderly: analysis of the National Health Survey - Danielle Samara Tavares de Oliveira-Figueiredo; Mariana Santos Felisbino-Mendes; Deborah Carvalho Malta; Jorge Gustavo Velásquez-Meléndez (Rev Rene)
Objective: to verify the prevalence of functional disability to perform basic and instrumental activities of daily living in the elderly. Methods: this is a cross-sectional study using data from the National Health Survey,whose sample was 7,373 elderly. Results: the prevalence of functional incapacity for basic and instrumental activities was 8.4% (Confidence Interval 95.0%: 7.4-9.4) and 22.0% (Confidence Interval 95.0%: 20 , 4-23.6),respectively, being higher in females, in those older (>75) and without levels of education. Demographic aspects, such as lower age and male sex, attenuated the prevalence of disability. Conclusion: the elderly showed a higher prevalence of functional disability for instrumental activities such as shopping, administering finances, taking medicines and going out on their own.